The effects of typical organic ligands on the rhizosphere microbial community and metabolic processes of Sedum alfredii hance - Xuzheng Huang; Fengxin Kang; Rongfei Wei; Qingjun Guo (Journal of Environmental Chemical Engineering, 2026)

Soyasaponin A1 ameliorates metabolic dysfunction-associated steatohepatitis via potentially reinforcing hepatoprotective capacity of Akkermansia muciniphila, restoring intestinal barrier homeostasis, and putatively modulating wnt/β-catenin signaling pathway - Zenghui Qin; Qingjun Guo; Ke Zhang; Jiazhi Lu; Jiexian Wang; Zijun Li; Lingyun Zhong; Yiting Huang; Qing Li; Xiangyi Zheng; Huiyu Luo; Longying Zha (Food Bioscience, 2026)

The evolution, migration, and transformation of dissolved organic matter in black shale regions: environmental destination and implications - Yinbo Xu; Guangxu Zhu; Pei Xu; Changqiu Zhao; Rongfei Wei; Usman Kaku Dawuda; Qingjun Guo (Geochimica et Cosmochimica Acta, 2026)

Serendipita promotes seed germination and seedling development of the endangered orchid Mengzia foliosa under in vitro conditions - Xinhua Zeng; Yulin Pu; Shanmin Li; Qiaoning Ren; Chao Hu; Kai Jiang; Ting Guo; Qingjun Huang; Weichang Huang (Symbiosis, 2026)

Radiogenic and stable Nd isotopic signatures in pelagic sediments: implications for tracing Nd cycling in hydrothermal-influenced pelagic environments - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Hao Wu; Jiayi Ma; Qingjun Guo; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

The effects of typical amino acid ligands on Cd translocation and detoxification processes in hyperaccumulator Sedum alfredii Hance - Fengxin Kang; Rongfei Wei; Xuzheng Huang; Usman Kaku Dawuda; Pei Xu; Zhiying Li; Zhenghua Tao; Liyan Tian; Xiaoxue Ouyang; Qingjun Guo (Journal of Environmental Sciences, 2026)

Fate of dissolved organic matter in the wastewater treatment plant-constructed wetland system - Xin Li; Anning Li; Bentao Bao; Zejin Zhang; Shiyu Li; Xiaoyong Cui; Hans Christian Bruun Hansen; Qingjun Guo; Flemming Ekelund (Journal of Environmental Sciences, 2026)

Energy transition, innovation-driven, and green technological innovation—an empirical study based on double machine learning - Wen Li; Rui Gao; Qingjun Zeng; Xianpeng Guo (Environment, Development and Sustainability, 2026)

Study on stress sensitivity of clayey silt hydrate-bearing sediments and its influence law on production - Yongge Liu; Yipu Li; Zhaoxiang Zhang; Guo Li; Jian Hou; Chao Ma; Bei Wei; Qingjun Du; Mengfan Zhang; Yunkai Ji; Chunlin Wang; Zhangxing Chen (Water Research, 2026)

Transcriptome-based identification, cloning and functional characterization of the MYB-related transcription factor genes CmDIV-like and CmRAD1 in Chrysanthemum morifolium cv. ‘Hangju’ - Yujing Ma; Hong Zhang; Qingjun Zou; Qiaosheng Guo; Chengxiang Wang; Jingzhe Pu; Tao Wang (Plant Science, 2026)

Molecular-level mechanisms in amide-based porous polymers for selective copper adsorption: A DFT study with environmental applications - Feili Li; Tianzheng Ding; Jinxi Li; Yannian Liu; Jianhong Jia; Qingjun Guo (Environmental Research, 2026)

Decoding the role of fungal functional groups in dissolved organic matter transformation and humification during co-composting - Xin Li; Zejin Zhang; Fang Wang; Ting Li; Qingjun Guo; Xiaoyong Cui; Hans Christian Bruun Hansen; Rasmus Kjøller; Flemming Ekelund (Bioresource Technology, 2025)

A medicinal plant highly stable for survival under climate change due to UV buffering–Chrysanthemum indicum L. future adaptation analysis - Tingting Xie; Hongzhuan Shi; Qiaosheng Guo; Tao Wang; Qingjun Zou; Min Wei; Chang Liu; Jianmin Huang; Yong Su; Chenlu Yang (Flora, 2025)

The relationship between anaerobic oxidation of methane and dark carbon fixation in methane seep sediments - Yinan Deng; Rui Xie; Qingjun Guo; Shengxiong Yang; Ganglan Zhang; Hongfei Lai; Qianyong Liang; Fang Chen; Jun Cao (Global and Planetary Change, 2025)

Decoding PM2.5 oxidative potential in Ningbo, China: Key chemicals, sources, and health risks via dual-assay and machine learning - Lord Famiyeh; Ke Chen; Jingsha Xu; Fiseha Berhanu Tesema; Mosses Solomon; Dongsheng Ji; Honghui Xu; Chengjun Wang; Qingjun Guo; Conghua Wen; John L. Zhou; Jun He (Journal of Hazardous Materials, 2025)

Atomically dispersed noble metal-Ox sites for electrocatalytic chlorine evolution - Chen Chen; Baoyi Guo; Tingting Liu; Ruting Lin; Yuyu Liu; Qiufeng Huang; Xiaofeng Zhang; Jiabao Huang; Fangren Qian; Shengyun Huang; Qingjun Chen; Xueqin Mu; et al. (Chemical Engineering Journal, 2025)

Study on the migration pathway and isotopic composition of Zn in soil, plant and water in mining area - Jing Kong; Qingjun Guo; Rongfei Wei; Ou Sha; Mingyan Mao; Suchang Yang (Journal of Hazardous Materials, 2025)

The multifaceted nature of SUMOylation in heart disease and its therapeutic potential - Ying He; Zhijie Yang; Dan Guo; Cheng Luo; Qiaoqiao Liu; Lei Xian; Fan Yang; Chusheng Huang; Qingjun Wei (Molecular and Cellular Biochemistry, 2025)

A study on influencing factors of port cargo throughput based on multi-scale geographically weighted regression - Ruitong Guo; Guangnian Xiao; Chunqin Zhang; Qingjun Li (Frontiers in Marine Science, 2025)
Port cargo throughput plays a pivotal role in driving national economic growth, facilitating trade activities, and promoting urban development. This study employs a Multi-scale Geographically Weighted Regression (MGWR) model to analyse the influencing factors of port cargo throughput, with regional Gross Domestic Product (GDP), highway construction investment, waterway construction investment, total import and export volume of goods, total retail sales of consumer goods, number of port berths, and urban residents’ consumption expenditure as independent variables. Based on data collected from 43 ports across China, the research reveals the magnitude and spatial distribution characteristics of these variables’ impacts on port cargo throughput. By comparing the fitting results of the global regression model with those of local regression models, the study demonstrates that the MGWR model achieves superior local regression fitting compared to the fixed-bandwidth Geographically Weighted Regression (GWR) model. This research provides theoretical support for understanding the spatial heterogeneity of factors influencing port cargo throughput and offers actionable insights for policy formulation and port planning.

Enhancing pepper resistance to MEAM1 whiteflies: the role of BABA as a chemical priming agent - Helong Zhang; Haobo Guo; Yaqi Wen; Qingjun Wu; Youjun Zhang; Xiaoguo Jiao (Journal of Pest Science, 2025)

Terrestrial pyrite oxidation point to carbon cycle: Insights from sulfur and oxygen isotope composition in rivers - Huiying Hu; Changqiu Zhao; Sen Xu; Rongfei Wei; Qiang Wei; Qiyu Tan; Qingjun Guo (Journal of Hydrology, 2025)

Creatine in giant grouper (Epinephelus lanceolatus): Insights into biosynthesis and transporter genes molecular characterization, regulation and impact on muscle metabolism - Yuejia Sun; Zhi Zheng; Dingqian Guo; Yao Wang; Qingjun Wu; Yujie Gao (Aquaculture, 2025)

Efficient remediation of different concentrations of Cr-contaminated soils by nano zero-valent iron modified with carboxymethyl cellulose and biochar - Lihong Xie; Qiyan Ma; Qingjun Chen; Yiyang Liu; Pengfei Guo; Jinlan Zhang; Guilan Duan; Aijun Lin; Tingting Zhang; Shangyi Li (Journal of Environmental Sciences, 2025)

Study on the variation mechanism of Zn isotope in polluted farmland soil - Jing Kong; Fang Huang; Rongfei Wei; Xingchao Zhang; Guangxu Zhu; Qingjun Guo (Journal of Hazardous Materials, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

Corrigendum to “Size distribution and lung-depostion of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays” [Environ. Pollut. 336 (2023) 122437] - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2024)

Self-discharge of redox electrolyte enhanced supercapacitors based on nanosheet-like CoS2 - Huanchi Chen; Yuxuan Zhang; Huailin Yang; Bingzhe Jia; Xinming Wu; Qingjun Guo (Chemical Engineering Journal, 2024)

Hydrological dynamics and manganese mineralization in the wake of the Sturtian glaciation - Yuntao Ye; Xiaomei Wang; Huajian Wang; Haifeng Fan; Zhigang Chen; Qingjun Guo; Ziteng Wang; Chaodong Wu; Donald E. Canfield; Shuichang Zhang (Geochimica et Cosmochimica Acta, 2024)

Effect of NOX, O3 and NH3 on sulfur isotope composition during heterogeneous oxidation of SO2: a laboratory investigation - Zhaobing Guo; Qingxiang Qian; Mingyi Xu; Bin Zhu; Qingjun Guo; Pengxiang Qiu (Air Quality, Atmosphere & Health, 2024)

Mercury stable isotopes revealing the atmospheric mercury circulation: A review of particulate bound mercury in China - Xuechao Qin; Qingjun Guo; Pim Martens; Thomas Krafft (Earth-Science Reviews, 2024)

Profiling the selected hotspots for ear traits in two maize–teosinte populations - Xuanjun Feng; Huarui Guan; Ying Wen; Hanmei Zhou; Xiaobin Xing; Yinzhi Li; Dan Zheng; Qingjun Wang; Weixiao Zhang; Hao Xiong; Yue Hu; Li Jia; et al. (Theoretical and Applied Genetics, 2024)

Global scale identification of catchments phosphorus source shifts with urbanization: A phosphate oxygen isotope and Bayesian mixing model approach - Ziteng Wang; Fuhong Sun; Qingjun Guo; Daren C. Gooddy; Fengchang Wu (Water Research, 2024)

Estimating atmospheric nitrogen deposition within a large river basin using moss nitrogen and isotope signatures - Chenjun Du; Qingjun Guo; Pengcheng Wu; Zhaoqin Yi; Rongfei Wei; Xinyuan Dong; Teklit Zerizghi; Ziteng Wang; Jun Zhang (Chemosphere, 2024)

Breathing in danger: Unveiling the link between human exposure to outdoor PM2.5-bound polycyclic aromatic hydrocarbons and lung cancer risk in an urban residential area of China - Lord Famiyeh; Honghui Xu; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Hang Xiao; Lei Tong; Chunrong Jia; Qingjun Guo; Jun He (Science of The Total Environment, 2024)

The negative-positive feedback transition thresholds of meteorological drought in response to agricultural drought and their dynamics - Xiaoting Wei; Shengzhi Huang; Jianfeng Li; Qiang Huang; Guoyong Leng; Dong Liu; Wenwen Guo; Xudong Zheng; Qingjun Bai (Science of The Total Environment, 2024)

Phosphate oxygen isotopes constrain Mesoproterozoic marine temperatures and the paucity of phosphorite - Yuntao Ye; Xiaomei Wang; Huajian Wang; Haifeng Fan; Zhigang Chen; Qingjun Guo; Ziteng Wang; Chaodong Wu; Donald E. Canfield; Shuichang Zhang (Chemical Geology, 2024)

Legacy phosphorus delays the accomplishment of expected phosphorus management object - Ziteng Wang; Qingjun Guo; Rongfei Wei (Journal of Environmental Management, 2023)

Size distribution and lung-deposition of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2023)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

Partition pattern and environmental consequences of the widespread coalmines and host rocks on the water of selected regions, China - Rahib Hussain; Kunli Luo; Qingjun Guo (Environmental Geochemistry and Health, 2023)

Source partitioning using phosphate oxygen isotopes and multiple models in a large catchment - Ziteng Wang; Liyan Tian; Changqiu Zhao; Chenjun Du; Jun Zhang; Fuhong Sun; Teklit Zerizghi Tekleab; Rongfei Wei; Pingqing Fu; Daren C. Gooddy; Qingjun Guo (Water Research, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

Isotopic signatures unveil the lead sources and migration in surface mangrove sediments - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Jingli Liu; Yanping Li; Hao Jiang; Yongyan Liao; Ke Pan (Science of The Total Environment, 2023)

Control mechanisms of water chemistry based on long-term analyses of the Yangtze River - Huiying Hu; Rongfei Wei; Teklit Zerizghi; Chenjun Du; Changqiu Zhao; Ziteng Wang; Jun Zhang; Qiyu Tan; Qingjun Guo (Science of The Total Environment, 2023)

Assessment of the role of an ABCC transporter TuMRP1 in the toxicity of abamectin to Tetranychus urticae - Mingmei Wu; Yan Zhang; Tian Tian; Dandan Xu; Qingjun Wu; Wen Xie; Youjun Zhang; Neil Crickmore; Zhaojiang Guo; Shaoli Wang (Pesticide Biochemistry and Physiology, 2023)

Rare earth elements in soil around coal mining and utilization: Contamination, characteristics, and effect of soil physicochemical properties - Teklit Zerizghi; Qingjun Guo; Rongfei Wei; Ziteng Wang; Chenjun Du; Yinan Deng (Environmental Pollution, 2023)

Impacts of mining activities on the spatial distribution and source apportionment of soil organic matter in a karst farmland - Jun Zhang; Rongfei Wei; Qingjun Guo (Science of The Total Environment, 2023)

A comprehensive method of source apportionment and ecological risk assessment of soil heavy metals: A case study in Qingyuan city, China - Rongfei Wei; Zirui Meng; Teklit Zerizghi; Jie Luo; Qingjun Guo (Science of The Total Environment, 2023)

Effect of dietary bile acids supplementation on growth performance, feed utilization, intestinal digestive enzyme activity and fatty acid transporters gene expression in juvenile leopard coral grouper (Plectropomus leopardus) - Yujie Gao; Yifan Yao; Jie Huang; Yuejia Sun; Qingjun Wu; Dingqian Guo; Shengpeng Wang (Frontiers in Marine Science, 2023)
This study aimed to evaluate the effects of dietary bile acids on growth performance, feed utilization, body composition, digestive enzyme activity, and related gene expression in juvenile leopard coral grouper ( Plectropomus leopardus ). Five diets with varying levels of dietary bile acids (0, 0.15, 0.3, 0.45 and 0.6%) were formulated and each diet was fed to triplicate groups of 15 fish (13.14 ± 0.14 g) for ten weeks. Results showed that the significant enhancement in weight gain (WG) and specific growth rate (SGR) was observed in fish fed 0.3% bile acids ( P < 0.05). Additionally, feed conversion ratio (FCR) was significantly improved with bile acids inclusion ( P < 0.05). Higher feed intake was also recorded in bile acids inclusion groups, and significantly up-regulated gene expression of hypothalamus neuropeptide Y (NPY) was found in 0.3% group compared with the control group ( P < 0.05). Dietary bile acids (0.3%) significantly decreased lipid deposition in the whole-body ( P < 0.05), and lower hepatosomatic index (HSI) and viscerosomatic index (VSI) were also found in this group. Moreover, intestinal trypsin and lipase activities were significantly increased in 0.3% group ( P < 0.05) to promote feed digestion. In addition, the relative expression levels of intestinal fatty acid binding protein 2 (FABP2) significantly up-regulated with inclusion of dietary bile acids, suggesting an enhancement of fatty acid transport ( P < 0.05). In contrast, cholesterol transport related genes NPC1 like intracellular cholesterol transporter 1 (NPC1L1) and CD36 were notably down-regulated as bile acids inclusion ( P < 0.05). This study provides valuable information for the formulation of diets for juvenile coral trout and indicates that dietary bile acids could potentially be used to improve growth performance and feed utilization.

Slight transition in Chinese atmospheric Pb isotopic fingerprinting due to increasing foreign Pb - Zhenghua Tao; Qingjun Guo; Congqiang Liu; Rongfei Wei; Xiaokun Han; Yunchao Lang; Zhaobing Guo; Jian Hu; Xinyuan Dong; Lord Famiyeh (Environmental Pollution, 2023)

The CmMYB3 transcription factors isolated from the Chrysanthemum morifolium regulate flavonol biosynthesis in Arabidopsis thaliana - Feng Yang; Tao Wang; Qiaosheng Guo; Qingjun Zou; Shuyan Yu (Plant Cell Reports, 2023)

Tracing the transboundary transport of atmospheric Particulate Bound Mercury driven by the East Asian monsoon - Xuechao Qin; Xinyuan Dong; Zhenghua Tao; Rongfei Wei; Hua Zhang; Qingjun Guo (Journal of Hazardous Materials, 2023)

Nitrate sources and transformations along the Yangtze river and its changes after strict environmental regulation - Jun Zhang; Rongfei Wei; Teklit Zerizghi; Ziteng Wang; Meng Cui; Chenjun Du; Fujun Yue; Qingjun Guo (Journal of Hydrology, 2023)

Influence of arbuscular mycorrhizal fungi on bioaccumulation and bioavailability of As and Cd: A meta-analysis - Qiyu Tan; Qingjun Guo; Rongfei Wei; Guangxu Zhu; Chenjun Du; Huiying Hu (Environmental Pollution, 2023)

Variations and its driven factors of anthropogenic nitrogen loads in the Yangtze River Economic Belt during 2000–2019 - Meng Cui; Qingjun Guo; Yujun Wei; Xuening Yu; Jian Hu; Liyan Tian; Jing Kong (Environmental Science and Pollution Research, 2023)

Disentangling Diel Variations in the Carbon Isotopic Composition of Soil CO2 Efflux: Insights from a Multi-chamber System and a Non-Steady-State Model - Changhua Chen; Jie Wei; Jingyuan Wang; Qingjun Guo; Xuefa Wen (Journal of Soil Science and Plant Nutrition, 2022)

Short-term deformation characteristics, displacement prediction, and kinematic mechanism of Baijiabao landslide based on updated monitoring data - Wenmin Yao; Changdong Li; Yuancheng Guo; Robert E. Criss; Qingjun Zuo; Hongbin Zhan (Bulletin of Engineering Geology and the Environment, 2022)

Comparison of metabolome characteristics and screening of chemical markers in Chrysanthemum indicum from different habitats - Qingjun Zou; Qiaosheng Guo; Tao Wang; Jiamin Chen; Feng Yang; Chenlu Yang (Physiology and Molecular Biology of Plants, 2022)

Fused: a promising molecular target for an RNAi-based strategy to manage Bt resistance in Plutella xylostella (L.) - Shi Kang; Dan Sun; Jianying Qin; Le Guo; Liuhong Zhu; Yang Bai; Qingjun Wu; Shaoli Wang; Xuguo Zhou; Zhaojiang Guo; Youjun Zhang (Journal of Pest Science, 2022)

Vegetation recovery alters soil N status in subtropical karst plateau area: Evidence from natural abundance δ15N and δ18O - Jing Wang; Xuefa Wen; Sidan Lyu; Xinyu Zhang; Shenggong Li; Qingjun Guo (Plant and Soil, 2021)

Seasonal and long-term trends of sulfate, nitrate, and ammonium in PM2.5 in Beijing: implication for air pollution control - Xiaokun Han; Qingjun Guo; Yunchao Lang; Siliang Li; Ying Li; Zhaobing Guo; Jian Hu; Rongfei Wei; Liyan Tian; Yingxin Wan (Environmental Science and Pollution Research, 2020)

The mixing of multi-source fluids in the Wusihe Zn–Pb ore deposit in Sichuan Province, Southwestern China - Hongjie Zhang; Haifeng Fan; Chaoyi Xiao; Hanjie Wen; Lin Ye; Zhilong Huang; Jiaxi Zhou; Qingjun Guo (Acta Geochimica, 2019)

A Study on Particle Suspension Flow and Permeability Impairment in Porous Media Using LBM–DEM–IMB Simulation Method - Kang Zhou; Jian Hou; Qicheng Sun; Lanlei Guo; Shaoxian Bing; Qingjun Du; Chuanjin Yao (Transport in Porous Media, 2018)

Sulfate sources constrained by sulfur and oxygen isotopic compositions in the upper reaches of the Xijiang River, China - Jing Liu; Siliang Li; Jun Zhong; Xuetao Zhu; Qingjun Guo; Yunchao Lang; Xiaokun Han (Acta Geochimica, 2017)

Gamma irradiation-induced decomposition of sulfamethoxazole in aqueous solution: the influence of additives, biological inhibitory, and degradation mechanisms - Jinjin Wang; Ziyan Guo; Xiaoyu Shen; Qingjun Guo; Yongfu Zhao; Shengnan Zhu; Zhaobing Guo (Environmental Science and Pollution Research, 2017)

Characteristics, source, and potential ecological risk assessment of polycyclic aromatic hydrocarbons (PAHs) in the Songhua River Basin, Northeast China - Jian Hu; Congqiang Liu; Qingjun Guo; Junxin Yang; Chukwunonso Peter Okoli; Yunchao Lang; Zhiqi Zhao; Siliang Li; Baojian Liu; Guangwei Song (Environmental Science and Pollution Research, 2017)

Multivariate statistical and lead isotopic analyses approach to identify heavy metal sources in topsoil from the industrial zone of Beijing Capital Iron and Steel Factory - Guangxu Zhu; Qingjun Guo; Huayun Xiao; Tongbin Chen; Jun Yang (Environmental Science and Pollution Research, 2017)

Phosphorus removal from aqueous solution in parent and aluminum-modified eggshells: thermodynamics and kinetics, adsorption mechanism, and diffusion process - Ziyan Guo; Jiuhai Li; Zhaobing Guo; Qingjun Guo; Bin Zhu (Environmental Science and Pollution Research, 2017)

Research and application of method of oxygen isotope of inorganic phosphate in Beijing agricultural soils - Liyan Tian; Qingjun Guo; Yongguan Zhu; Huijun He; Yunchao Lang; Jian Hu; Han Zhang; Rongfei Wei; Xiaokun Han; Marc Peters; Junxing Yang (Environmental Science and Pollution Research, 2016)

Chemical and sulfur isotopic composition of precipitation in Beijing, China - Guangxu Zhu; Qingjun Guo; Tongbin Chen; Yunchao Lang; Marc Peters; Liyan Tian; Hanzhi Zhang; Chunyu Wang (Environmental Science and Pollution Research, 2016)

Differing effects of cabbage and pepper on B and Q putative species of Bemisia tabaci - Xiaoguo Jiao; Wen Xie; Litao Guo; Baiming Liu; Shaoli Wang; Qingjun Wu; Youjun Zhang (Journal of Pest Science, 2014)

FY-3A/MERSI, ocean color algorithm, products and demonstrative applications - Ling Sun; Maohua Guo; Jianhua Zhu; Xiuqing Hu; Qingjun Song (Acta Oceanologica Sinica, 2013)